Personification as a Reflection of Sadness: A Socio-Cultural Stylistic Study in Natsume Soseki's Kokoro Novel - Fairuz Fairuz; Belia Mala Sari (Hasanuddin University, 2025)
Kokoro novel by Natsume Soseki depicts the emotional struggle and loneliness of its characters amidst the pressure of Japan's socio-cultural transformation in the Meiji era, namely the shift from tradition to modernity. The characters' deep sadness is often expressed through the style of personification, making inanimate objects and natural atmospheres seem to have feelings, as a stylistic reflection rich in meaning. This study aims to identify the forms and imagery of personification that reflect the sadness of the main character and analyze the relationship between personification and the socio-cultural context of the Meiji era as a form of response to modernization. The study uses a cognitive stylistic approach (based on Lakoff & Johnson) and a sociocultural approach to see the relationship between language style and the context of changes in community values. The descriptive-qualitative method is carried out through the identification of personification quotes, classification of types, and interpretation of emotional meaning and its relationship to socio-cultural phenomena. The results of the study show that personification appears in nature (wind, sky, rain, fog) and the city atmosphere which emphasizes sadness and alienation. Personification also serves as a medium for emotional expression of characters as well as a subtle critique of socio-cultural turmoil, showing how language constructs and voices emotions in a particular historical context. Through the personification of objects and atmosphere, Natsume Soseki conveys sadness, isolation and anxiety in a society caught in the current of modernization.